The Political Practice of Identity in the Dynamics of Local Politics Gayo Society - Wantona, Saradi; A. Kinseng, Rilus; Sjaf, Sofyan (Sodality: Jurnal Sosiologi Pedesaan, 2018)
ABSTRACTThe objective of this research is to analyze the politic actors in playing their capital in local politic contestation, both at regent level also at rural level in Central Aceh. The study approach uses teory of Bordieu habitus, also uses qualitative method for arena and capital then supported by quantitative data. Analysis unit of this research is politic actors who followed headed of regent’s election in 2012. The data taken by using in depth interview technique and literature analysis of historical documents. Result of the research show that first, dominant capital who played by politic actors in constitution of local politic is capital politic, social and economic. Second, the political practice of identity in Gayo Society that propagandize term of uken-toa doing by politic actors, whereas in grass community sentiment of identity between uken and toa do not evolve and fade as time goes by. Third, habitus of politic actors are influenced by three things, those are history, religion and culture. Therefore, the condition of habitus that play a role in politic contestation is historical formation of uken and toa identity in the past and influence politic of conflict which doing by Dutch colonists.Keywords : Identity practice, dynamics of local politics, arena, capital, habitus, actors and Gayo ethnicityABSTRAKPenelitian ini bertujuan untuk menganalisis aktor politik dalam memainkan modal mereka dalam kontestasi politik lokal, baik di tingkat kabupaten maupun di pedesaan di kabupaten Aceh Tengah. Pendekatan riset ini menggunakan teori Bordieu, habitus, arena dan modal dengan menggunakan metode kualitatif dan didukung oleh data kuantitatif. Unit analisis dari penelitian ini adalah aktor politik yang mengikuti pemilihan kepala daerah pada tahun 2012. Pengambilan data dilakukan dengan teknik wawancara mendalam dan analisis literatur dokumen sejarah. Hasil penelitian menunjukkan bahwa pertama; modal dominan yang dimainkan aktor politik dalam kontestasi politik lokal adalah modal politik, modal sosial dan modal ekonomi. Kedua, praktik politik identitas dalam masyarakat Gayo yang mempropagandakan istilah uken- toa dilakukan oleh aktor politik, sedangkan di akar rumput sentimen identitas antara uken dan toa tidak lagi berkembang dan sudah memudar seiring perkembangan waktu. Ketiga, habitus aktor politik dipengaruhi oleh tiga hal, sejarah, agama, dan budaya. Dengan begitu, kondisi habitus yang berperan dalam kontestasi politik adalah sejarah pembentukkan identitas uken dan toa di masa lalu dan pengaruh politik adu domba yang dilakukan kolonial Belanda.Kata kunci: Praktik identitas, dinamika politik lokal, arena, modal, habitus, aktor, dan etnik Gayo